2002
DOI: 10.1055/s-2002-34857
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polyfluorinated Tertiary Alcohols Using Ring Opening Reactions of 2,2-Bis(trifluoromethyl)oxirane

Abstract: This paper describes new reactions of 2,2-bis(trifluoromethyl)oxirane (1). Ring opening of 1 by oxygen, nitrogen, sulfur or carbon nucleophiles (Nu -) proceeds regioselectively, with exclusive formation of tertiary alcohols: NuCH 2 C(CF 3 ) 2 OH. The reaction of 1 with strong acids (HX) is also regioselective and proceeds under mild conditions leading to the formation of XCH 2 C(CF 3 ) 2 OH (X = FSO 2 O, CF 3 SO 2 O, Cl, I). The addition of acetic acid to 1, however, requires an elevated temperature and TaF 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…It was also reported that 31 and ammonium hydroxide at ambient temperature undergo a threefold reaction to give tris(3,3,3-trifluoro-2-hydroxypropyl)amine [34]. Under similar conditions, the reaction of 2,2-bis(trifluoromethyl)oxirane (34) and ammonia or ammonium hydroxide yield β-amino-α,α-bis(trifluoromethyl)ethanol as the major product [35]. As a minor product, the secondary amine with two 2-hydroxy- In situ generated 34 (two mol.-equiv.)…”
Section: Ring Opening Of Trifluoromethyloxiranes With N-nucleophilesmentioning
confidence: 89%
“…It was also reported that 31 and ammonium hydroxide at ambient temperature undergo a threefold reaction to give tris(3,3,3-trifluoro-2-hydroxypropyl)amine [34]. Under similar conditions, the reaction of 2,2-bis(trifluoromethyl)oxirane (34) and ammonia or ammonium hydroxide yield β-amino-α,α-bis(trifluoromethyl)ethanol as the major product [35]. As a minor product, the secondary amine with two 2-hydroxy- In situ generated 34 (two mol.-equiv.)…”
Section: Ring Opening Of Trifluoromethyloxiranes With N-nucleophilesmentioning
confidence: 89%
“…Crude reaction product was transferred out of the reactor under vacuum at 20-30 8C (250-50 mmHg) in a cold trap (at À78 8C). The crude product was dried over MgSO 4 and distilled to give a 33 g (yield 75%) of 1a, bp 41-42 8C at 760 mmHg (reported), bp 41-42 8C [5,20] and 39 8C [18]. Reaction conditions, analytical, NMR and IR data for epoxides 1a, 2a, 3a, 5a are given in Tables 1 and 2. 4.1.4.2.…”
Section: Synthesis Of 2-trifluoromethyl-44333-pentafluoroethylbutmentioning
confidence: 99%
“…The known [17] exo-acetate, prepared by addition of acetic acid to norbornadiene, is hydrolyzed to the exo-alcohol. The sodium salt of the alcohol then reacts readily with hexafluoroisobutylene oxide [18] to afford NB-F-OH which polymerizes with TFE to give polymer with acceptable conversion and molecular weight.…”
Section: Polymerization Technologymentioning
confidence: 99%